When the border educates: Malín Alegria’s Sofi Mendoza’s Guide to Getting Lost in Mexico (2007) - Ibarraran-Bigalondo, Amaia (International Journal of English Studies, 2016)
The border between the United States and Mexico, since it was first conceived in 1848, has marked the lives of those who live on both of its sides, as well as of those who want to cross it. It has also become the source of a vast array of theoretical and artistic work. Chicano writers have written about it, and so have theorists dealt with its meaning and conceptual implications. The aim of this essay is to observe the way Malín Alegrías Sofi Mendoza’s Guide to Getting Lost in Mexico (2007), a novel for young adults, serves as a way for young adults to “evolve a moral consciousness” (Scharf 1980), through a process of “critical witnessing” (López 2009) of what it means to be on one or the other side of la frontera.